Efficacy and Tolerability of a New Formulation in Rectal Ointment Based on Zn-L-Carnosine (Proctilor®) in the Treatment of Haemorrhoidal Disease - Pietroletti, Renato; Giuliani, Antonio; Buonanno, Alberto; Mattei, Antonella; Fiasca, Fabiana; Gallo, Gaetano (Frontiers in Surgery, 2022)
Haemorrhoidal disease (HD) shows high prevalence in western countries, reaching 4.4% per year in the US. Topical preparations are the first-line treatments, which are readily available as “over-the-counter” (OTC) products, often containing a nonstandardised mixture of “natural” remedies, or anaesthetics or cortisol;those latter are not free from undesirable effects. The Zinc-L-Carnosine is a cytoprotective compound, promoting mucosal repair in the gastrointestinal tract and also in mucosal repair, following radiation injuries to the rectum as well as in ulcerative colitis. Our aim was to study the efficacy of Zinc-L-Carnosine in relieving acute symptoms of HD, testing a preparation in the rectal ointment, Proctilor®, in patients complaining of bleeding or thrombosed piles. In a multicentre open trial, 21 patients older than 18 years of age were enrolled. The symptoms of HD were graded according to the Haemorrhoidal Disease Symptoms Score (HDSS) in association with the Short Health Scale (SHS) to assess the influence of HD on quality of life. The pain was assessed with the VAS score, bowel habit by means of the Bristol scale. The patients were evaluated at enrolment (T0) and 2 (T1) and 4 (T2) weeks of treatment with Proctilor® rectal ointment. There were 10 men and 11 women; mean age, 49 years. Pain, bleeding, and thrombosis were all significantly reduced after treatment; the mean VAS score decreased from 4.71 ± 3.05 at T0 to.52 ± 0.87 and.05 ± 0.22 at T1 and T2, respectively; (mean ± SD; p < 0.001 in both cases). Similarly, the HDSS score showed to be significantly reduced between T0, T1 (8.05 ± 4.55 vs. 1.14 ± 1.01), and T2 (8.05 ± 4.55 vs. 24 ± 0.44) (mean ± SD; p < 0.001 in both cases). Quality of life showed to be improved as the SHS score decreased significantly with treatment (7.90 ± 4.17 at T0 vs. 4.24 ± 0.44 at T1 vs. 4.05 ± 0.22 at T2; mean ± SD; p < 0.001 in both cases). The Bristol score of defecation remained substantially unchanged. No side effects or discontinuation of treatment were reported. Results of our investigation suggest a role of Proctilor® rectal ointment in treating symptomatic HD with good results and an excellent safety profile. However, our preliminary results encourage further studies on a larger number of patients to confirm the role of Zinc-L-Carnosine in the rectal ointment for the topical treatment of HD.